A comparative study on gamification of the flipped classroom in engineering education to enhance the effects of learning. Issue 5 (28th June 2018) - Jo, Jaechoon; Jun, Heeyeon; Lim, Heuiseok
Abstract: This study analyzes the effectiveness of adding educational gaming elements into the online lecture system of the flipped classroom as a method to increase participation and interest in online preparation before class. This study held an "understanding sequence" for 20 classes during the 7‐week automation equipment class with 30 s year high school students in Incheon's specialized technical high school as target. After the class, the learning attitude of learners was measured through surveys and in‐depth interviews. As a result, first, it was found that the degree of preparation participation in flip learning using gaming elements had a statistically significant increase from 65.56% to 78.89%, compared with the traditional flip learning using YouTube. Second, comparing the academic achievements showed a diagnostic assessment of 57.44 before applying the gaming elements and 20.17 after the application. However, for summative assessment, the degree after applying gaming elements was statistically higher at 84.52 than the degree before application, which was 78.86. Third, comparing academic achievement with word game results showed no significant correlation, and it is judged that all students were able to enjoy word games, regardless of their grades. Also, when the average word game scores were compared based on students' grades, mid‐upper level students had statistically significant higher scores than upper level students. Lastly, analysis on the correlation between attitude and word game showed that there is a quantitatively high correlation between the ranking system's competitive spirit and interest. The ranking system increased competitive spirit, as well as interest.